Efektivitas Training of Organization Leadership pada Penanaman Etos Kerja Anggota ICIS Universitas Islam Negeri Khas Jember - Hafidzatul Mu’tamiroh; Nonik Arselina; Sisca Ruwaida Lutfiah Amin; Aniqotuzzuhro’ Fitriana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
The large number of members is a separate threat to the survival of an organization. Therefore, it is necessary to choose quality human resources so that the organization continues to run well. Good resources also need planting and supporting education. Thus the author is interested in conducting research on the existence of a Training of Organizational Leadership agenda held by the ICIS UIN KHAS Jember organization to instill various organizational matters in its members. This type of research is descriptive qualitative research with data collection using interviews and observation. The results of the study show that the inculcation of a work ethic in members of the ICIS UIN KHAS Jember organization through Training of Organizational Leadership can be said to be effective and have a considerable influence. This is evident in the formation of better identity and personality for members, as well as matters directly related to how a leader is able to apply or realize the theory obtained from the Training of Organizational Leadership.